Strategy orientation and government regulation on environmental performance: The role of green supply chain management - Maheswari, Uma (Journal of Management and Business Insight, 2023)
Purpose-Both internal and external factors may affect a business's environmental performance. Using green supply chain management as a mediating variable, this study examined the relationship between strategy orientation and government legislation on environmental performance. Design/Methodology/Approach-The study population focused on micro, small, and medium sized enterprises in Asia. This research data was collected through questionnaires given to respondents and obtained results as many as 50 respondents. Then, a model analysis was applied using the Smart PLS application. Findings-The findings demonstrate that government policies and initiatives have a direct and favorable impact on green supply chain management. Green supply chain management has a favorable impact on environmental performance however, government plans and regulations do not directly improve environmental performance. The results indicate that the impact of government strategy and regulatory orientation on environmental performance is mediated by green supply chain management. Research limitations/implications-For business actors, especially micro, small, and medium enterprises, it is necessary to focus on to the orientation of government strategies and regulations in their operational activities to encourage improved environmental performance. To support this, business actors must also pay attention to other factors, such as green supply chain management, to maximize efforts to achieve environmental performance. Originality/value There is currently a dearth of research on the environmental performance of businesses, particularly micro, small, and medium-sized businesses. Prior studies on environmental performance have examined both internal and external corporate aspects, such as strategy orientation and green supply chain management, as well as government requirements.